The Identification of Cultural Landscapes That Form Spatial Patterns in Gelgel Village, Klungkung - Mahadewi, Tjokorda Istri Agung Ray Sri; Kohdrata, Naniek (Journal of A Sustainable Global South; Vol 8 No 1 (2024): February 2024, 2024)
Gelgel is a village located in Klungkung regency, Bali. The landscape has a long historical background that can be traced back to the Bali kingdom era. The Gelgel cultural landscape has been certainly experienced changes from time to time. From the landscape architecture perspective, the socio-cultural changes throughtout the time will create spatial patterns that relates with the spatial functions. The imprint a spatial pattern can be useful for present and future spatial planning and space utilization. Therefore, it is necessary to carry out research to identify the types of cultural landscapes as well as the layout and function of cultural landscape spaces in Gelgel Village. The research uses qualitative methods to direct the process of data collection techniques that are observation, in-depth interviews, and literature study. This research aims to find the spatial layout and functions based on the indentified cultural landscape in Gelgel village. The research shows that the cultural landscape in Gelgel Village consists of four major cultural elements that are social systems and organizations, livelihoods, arts, and religious systems and ceremonies. Those cultural elements found can be categorized into tangible and intangible cultural landscapes. Laying out the identified cultural landscapes spatially shows that the modern Gelgel village spatial pattern is centered. Even though the pattern is centralistic, the area division is still based on parahyangan, pawongan, and palemahan zoning system imbued from the Balinese philosophy Tri Hita Karana . Each area functions according to the Tri Hita Karana philosophy that guides the Balinese harmonious life with God, people, and the environment.